Meropenem VS Cefoperazone Prophylaxis for Prevention of Surgical Site Infection In Colorectal Surgery (International Journal of Scientific Research and Management (IJSRM), 2017)
Introduction: Surgical site infection (SSI) is a potentially morbid complication following both elective as well as emergency operations. This increases the overall expenditure to the patient and health care system. Colorectal surgeries in particular are associated with increased incidence of SSI.Antimicrobial prophylaxis reduces the rate of SSI, but the choice of antibiotic is not yet established. Methods : This was a prospective study at a high volume centre for colorectal surgery in a tertiary care institute. All patients who underwent colorectal surgery in both elective as well as emergency settings were included in the study & allocated randomly to receive either meropenem or cefoperazone as prophylactic antibiotic and compare the rate of SSI in two groups. Result: A total of 538 patients were included, 316 (58.7%) were males while 222 (41.3%) were females. Mean age of the patients was 47.36±15.57 years. Elective procedures contributed for 84.01% (452) while 15.98% (86) cases were performed as emergency procedures. 67 out of 452 (14.8%) patients developed SSI in elective settings ,whileas 31 out of 86 (36.0%) patients developed SSI in emergency settings. There is a decreased rate of SSI in the cases where meropenem (9%) was administered as compared to cefeparozone (19.8%) (P value < 0.001). Conclusion: The incidence of SSI in colorectal surgeries is substantial, which leads to significant morbidity to the patients and the healthcare system. Meropenam is superior to cefoperazone in prevention of surgical site infection in patients following elective colorectal surgery